Advisory Committee on Climate Change Policy: A Committee of the American Statistical Association. Issue 1 (2nd January 2023) - Risser, Mark; Pierson, Steve
Abstract: This article describes the work of the American Statistical Association (ASA) Advisory Committee on Climate Change Policy (ACCP) which was established in 2008. The committee's earliest activities included meetings with Congressional committee staffers to hear firsthand their views on climate change, how or whether it should be addressed, and how the statistical perspective may be helpful. Building on the successes in raising awareness on Capitol Hill and beyond regarding the reality of climate change, the group is now pivoting to an emphasis on promoting solutions to climate change. These new efforts will ultimately enable statisticians and data scientists to engage more deeply in the research that is critical to society proactively and successfully addressing the intensifying impacts of climate change.